Recent advances in orally administered cell-specific nanotherapeutics for inflammatory bowel disease - Si, Xiao-Ying (World J Gastroenterol, 2016)
Inflammatory bowel disease (IBD) is a chronic relapsing disease in gastrointestinal tract. Conventional medications lack the efficacy to offer complete remission in IBD therapy, and usually associate with serious side effects. Recent studies indicated that nanoparticle-based nanotherapeutics may offer precise and safe alternative to conventional medications via enhanced targeting, sustained drug release, and decreased adverse effects. Here, we reviewed orally cell-specific nanotherapeutics developed in recent years. In addition, the various obstacles for oral drug delivery are also reviewed in this manuscript. Orally administrated cell-specific nanotherapeutics is expected to become a novel therapeutic approach for IBD treatment.